Duodenal expression of iron transport molecules in untreated haemochromatosis subjects. Issue 7 (1st July 2003) - Stuart, K A; Anderson, G J; Frazer, D M; Powell, L W; McCullen, M; Fletcher, L M; Crawford, D H G
Abstract : Background and aims: In HFE associated hereditary haemochromatosis, the duodenal enterocyte behaves as if iron deficient and previous reports have shown increased duodenal expression of divalent metal transporter 1 ( DMT1 ) and iron regulated gene 1 ( Ireg1 ) in affected subjects. In those studies, many patients had undergone venesection, which is a potent stimulus of iron absorption. Our study investigated duodenal expression of DMT1 ( IRE and non- IRE ), Ireg1, hephaestin, and duodenal cytochrome-b ( Dyctb ) in untreated C282Y homozygous haemochromatosis patients, iron deficient patients, and iron replete subjects. Methods: Total RNA was extracted from duodenal biopsies and expression of the iron transport genes was assessed by ribonuclease protection assay. Results: Expression of DMT1 ( IRE ) and Ireg1 was increased 3–5-fold in iron deficient subjects compared with iron replete subjects. Duodenal expression of DMT1 ( IRE ) and Ireg1 was similar in haemochromatosis patients and iron replete subjects but in haemochromatosis patients with elevated serum ferritin concentrations, both DMT1 ( IRE ) and Ireg1 expression were inappropriately increased relative to serum ferritin concentration. Hephaestin and Dcytb levels were not upregulated in haemochromatosis. DMT1 ( IRE ) and Ireg1 levels showed significant inverse correlations with serum ferritin concentration in each group of patients. Conclusions: These findings are consistent with DMT1 ( IRE ) and Ireg1 playing primary roles in the adaptive response to iron deficiency. Untreated haemochromatosis patients showed inappropriate increases in DMT1 ( IRE ) and Ireg1 expression for a given level of serum ferritin concentration, although the actual level of expression of these iron transport genes was not significantly different from that of normal subjects.